Neonatal mortality in infants with low birth weigh - Gaiva,Maria Aparecida Munhoz (2014)
Objective To evaluate the factors associated with neonatal mortality in infant born with low birth weight. Method Cross-sectional study that analyzed data from 771 live births with low birth weight (<2500 g) in the city of Cuiabá, MT, in 2010, of whom 54 died in the neonatal period. We obtained data from the Information System on Live Births and Mortality, by integrated linkage. Results In multiple logistic regression, neonatal mortality was associated with: number of prenatal visits less than 7 (OR=3.80;CI:1,66-8,70); gestational age less than 37 weeks (OR=4.77;CI:1.48-15.38), Apgar score less than 7 at the 1st minute (OR=4.25;CI:1.84-9.81) and the 5th minute (OR=5.72,CI:2.24-14.60) and presence of congenital anomaly (OR=14.39;IC:2.72-76.09). Conclusion Neonatal mortality in infants with low birth weight is associated with avoidable factors through adequate attention to prenatal care, childbirth and infants.